PROSEDUR PEREKRUTAN KARYAWAN PADA PT. PERMITA WAHYU MULYO MEDAN - Stefani Siregar, Yohana; Bahagia Mendrofa, Hendra Umbu (EDUTECH CONSULTANT, 2019)
Human resources are very opposed to companies, both small companies and large companies because of human resources in this case the workforce is a planner, requires and determines the realization of organizational goals. A very tight source of human competition requires an increase in the quality of human resources that will determine the success of the company in an effort to achieve success. To get employees who are disciplined, qualified, reliable, dynamic and full of dedication must go through the right employee recruitment procedure. Recruitment is the process of finding, finding, inviting and assigning people as prospective workers with certain characteristics that have been determined in human resource planning to work in an organization. In order to be able to recruit and eventually produce good and qualified employees, the procedure for hiring employees is very important in recruiting. Employee recruitment procedures are the steps used to recruit employees, by involving good recruitment procedures used in recruitment it will produce good prospective employees.